Effect of Seed Vigour on Field Performance and Seed Yield in Okra (Abelmoschus esculentus L.) - Keshavulu, K.; Reddy, N. Manohar; Rajeswari, B.; Kumar, M. Arun; Ankaiah, R. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was undertaken with freshly harvested seed of okra hybrid, Uphar, with different seed vigor levels after subjecting to accelerated ageing at 40 + 10C and 85 + 5 % relative humidity for 4, 8, 12 and 16 days to study the effect of seed vigor on initial seed quality, field performance and yield. The initial seed quality declined with increase in period of accelerated ageing. Plants established from low vigor seed lots exhibited poor field performance as evidenced by reduced plant height, reduction in dry matter production and leaf area per plant at different stages of crop growth, delay in days to 50 % flowering and days to first picking. The initial seed vigor levels exhibited a significant influence on yield and its contributing characters, but the same showed a declining trend with increase in duration of accelerated ageing.